Bleeding Events in Patients 75 Years of Age and Older Under Long-term Anticoagulant Therapy: A Real-life Study. Issue 3 (September 2020) - Conti, Alberto; Renzi, Noemi; Catarzi, Stefania; Mazzucchelli, Mariuccia; Covelli, Antonella; Pampana, Alessandro; Bongini, Giada; Bini, Giacomo; Leorin, Marco; Ghiadoni, Lorenzo
Abstract : Objective: To investigate the risk of bleeding events in older patients under oral anticoagulant with a 4-year survey of a catchment area with 197, 722 inhabitants of whom 15, 267 were on warfarin and 10, 397 on direct oral anticoagulants (DOACs). Methods: Patients presented to the Emergency Department with major bleeding were enrolled and stratified according to age ≥75 years and ongoing warfarin or DOACs. Primary endpoint was 1-month death. Results: Out of 1919 major bleeding, those of patients ≥75 years of age were 1127 (59%) versus 792 (41%) <75 years of age, P < 0.0001. In patients ≥75 years of age, brain hemorrhage accounted for 612 (54%) patients, gastrointestinal hemorrhage for 301 (27%), hematuria for 104 (9%), and other hemorrhage for 108 (10%). In patients ≥75 years of age, those on warfarin accounted for 175 versus 53 on DOACs, without difference of Charlson Comorbidity Index (5.25 ± 1.92 versus 5.09 ± 1.61; P = 0.5824). One-month death in patients ≥75 of age versus <75 years of age accounted for 77 (4.0%) versus 20 (1.0%); P < 0.0001. One-month death in patients ≥75 of age on DOACs was very low, without difference versus <75 years and within DOACs. Among DOACs, absolute bleeding events showed differences as follows: 3 bleeding events for edoxaban versus 21 for dabigatran; P < 0.001; versus 16 for rivaroxaban, P = 0.006; and versus 13 for apixaban, P = 0.02. Conclusions: Major bleeding and 1-month death accounted for higher percentage in patients ≥75 years of age and in patients receiving warfarin. Among DOACs, edoxaban presented the lowest absolute rate of hemorrhage among the 4 available DOACs, without difference in mortality.